Evaluation of Properties of Roller Compacted Concrete - Hamzah, Afrah A.; Al-Shadeedi, Mohammed Baqer (Nahrain University College of Engineering Journal, 2008)
The experimental and analytical behavior ofvarious mixes of roller compacted concrete (RCC) using different materials is presented in this work. This work is divided into two groups of experiments. In the first group a reference mix was prepared using local materials (cement, sand, aggregate). Mechanical and dynamic properties of reference mix with and without admixtures have been obtained. Also, this series includes a study of the various variables affecting the mechanical anddynamic properties of RCC. In this work, the effect of cement content, water/cement W/C ratio and type of aggregate on the mechanical properties has been studied. The optimum mixes which have good properties obtained from the first group of study were used in the second group. In this work, the effect of admixtures and type of admixtures (steel filings, metakaolin, fly ash, lime, rice husk and concrete wastes) on the mechanical properties has been studied. The analysis of results showed that using steel filings improves the mechanical properties when replacing the sand by steel filings in (5, 10, 15 and 20) % by weight. The ultimate compressive strength at 7 and 28 days is higher by 13.2 and 24.7%, respectively, than the compressive strength using sand only. Partial cement replacement by mineral admixtures like metakaolin with (10, 20 and 30) %, lime with (4, 6, 8, 10, 20 and 30) %, fly ash with (10, 20 and 30) % and rice husk with (4 and 8) % decreases the strength and other properties at early age of 28 days by about 12.02% when using metakaolin by 20% and about 12.5% when using lime by 10 %